The Scales Have Tipped: U.S. Marine Corps Boot Camp Increases Muscle Mass and Reduces Body Fat in Recruits - Emily Kloss; Daniel Bennett; Andrea C Givens; Brenda Niederberger; Laura Palombo; Karen R Kelly (Military Medicine, 2026)
Abstract Introduction The United States Marine Corps (USMC) enforces body composition standards to optimize readiness, reduce injury risk, and enhance lethality. While recruit screening has relied heavily on body mass index (BMI), this metric fails to capture simultaneous changes in fat mass (FM) and lean body mass (LBM) that occur during training. Limited data describe how male and female recruits physiologically adapt to boot camp relative to current age-dependent body fat percentage (BF%) standards. Materials and Methods One hundred sixty-one male and female USMC recruits completed body composition assessments at the beginning and following completion of boot camp. Body composition was measured using bioelectrical impedance analysis (InBody 770), the USMC-approved assessment tool. Outcomes included BMI, BF%, FM, LBM, and skeletal muscle mass (SMM). Results Boot camp produced favorable shifts in body composition across the cohort, characterized by reductions in BF% (−4.1%) and FM (−2.9 kg), as well as increases in LBM (+1.9 kg) and SMM (+1.0 kg). Female recruits demonstrated significantly greater absolute improvements across all body composition metrics compared with males (P < .001), including larger reductions in BF% and FM and greater gains in LBM and SMM. Combined across both sexes, there was a significant decrease in BMI from pre- to post-boot camp (P < .001); there were no sex-specific differences in overall BMI or rate of change. The proportion of recruits meeting USMC BF% standards increased significantly from pre- to post-boot camp (P < .001), with nearly all recruits who were initially classified outside standards achieving compliance by completion of boot camp. Conclusions USMC boot camp functions as an intense physiological intervention that improves body composition and enhances readiness in both sexes. Female recruits underwent significant physiological training adaptations, reinforcing their capacity to meet and exceed body composition standards under standardized training conditions. These findings highlight the operational limitations of BMI-based screening and support the continued use of direct body composition assessment to more accurately evaluate recruit readiness, training effectiveness, and force lethality.